The Ups and Downs of the Declaration of Helsinki: The Case of the Placebo - María Fernanda Sabio (Perspectivas Metodológicas​)
The Declaration of Helsinki, adopted in 1964 by the World Medical Association, is an ethical benchmark for research involving human subjects. Throughout its successive revisions, it has faced debates and controversies around several of its articles. This paper discusses the case of placebo and the centrality of the 2000 version, together with its problematic 2002 Explanatory Note. It also mentions the successive modifications, which have not changed the centrality of the 2002 Note. In this analysis, we take up Nancy Fraser's proposal in her book “Cannibal Capitalism”, in which she describes the pressures exerted by corporations on regulations. The pharmaceutical industry and its lobby are an example of this. Some of the arguments put forward by placebo supporters and opponents are also presented.